Dilemmas of Peace and Justice in Mexico in Times of Democracy and Human Rights Crisis - Ulfgard, Rebecka Villanueva (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article reflects on dilemmas of peace and justice in Latin America, which is currently going through a crisis of democracy, in light of Sustainable Development Objective 16 (SDG 16). The objective of the article is to critically analyze some of the challenges present in the region that face the norms and principles underlying this objective. The article emphasizes the case of Mexico through the cases that have been marked in the country with regard to the fight for the justice of the victims of violence; Ayotzinapa, and Tlatlaya. Furthermore, it presents some criticisms of the new National Guard launched by the government of Andrés Manuel López Obrador. Effectively, it is possible to talk about a shadowy perspective regarding the full and authentic implementation of SDG 16, both in Mexico and in other parts of the region in times of rampant violence and insecurity.